Biochemical features of dye‐decolorizing peroxidases: Current impact on lignin degradation. (13th September 2020) - Catucci, Gianluca; Valetti, Francesca; Sadeghi, Sheila J.; Gilardi, Gianfranco
Abstract: Dye‐decolorizing peroxidases (DyP) were originally discovered in fungi for their ability to decolorize several different industrial dyes. DyPs catalyze the oxidation of a variety of substrates such as phenolic and nonphenolic aromatic compounds. Catalysis occurs in the active site or on the surface of the enzyme depending on the size of the substrate and on the existence of radical transfer pathways available in the enzyme. DyPs show the typical features of heme‐containing enzymes with a Soret peak at 404–408 nm. They bind hydrogen peroxide that leads to the formation of the so‐called Compound I, the key intermediate for catalysis. This then decays into Compound II yielding back Fe(III) at its resting state. Each catalytic cycle uses two electrons from suitable electron donors and generates two product molecules. DyPs are classified as a separate class of peroxidases. As all peroxidases they encompass a conserved histidine that acts as the fifth heme ligand, however all primary DyP sequences contain a conserved GxxDG motif and a distal arginine that is their characteristic. Given their ability to attack monomeric and dimeric lignin model compounds as well as polymeric lignocellulose, DyPs are a promising class of biocatalysts for lignin degradation that not only represents a source of valuable fine chemicals, but it also constitutes a fundamental step in biofuels production. Research efforts are envisioned for the improvement of the activity of DyPs against lignin, through directed evolution, ration protein design, or one‐pot combination with other enzymes to reach satisfactory conversion levels for industrial applications. Abstract : Dye‐decolorizing peroxidases can be exploited to degrade lignin and produce biofuel.